World Tribology Congress III, Volume 2 2005
DOI: 10.1115/wtc2005-63400
|View full text |Cite
|
Sign up to set email alerts
|

Research of New Factors Affecting Rolling Contact Fatigue Life

Abstract: Conventional life theory defines the rolling contact fatigue (RCF) life as being determined by the maximum contact pressure (P) and the total number of stress cycles (N). However, when the life test results of bearings were analyzed, it was found that there were cases where there was little correlation between the RCF life, maximum contact pressure and the number of stress cycles. An extensive investigation has revealed that the slip velocity is an additional factor that influences the RCF life of bearings. Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
26
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 0 publications
5
26
0
Order By: Relevance
“…Slip energy criteria have been linked to WSF, WSF occurring at areas of greatest PVmax. These areas have also been found to coincide with zones of highest concentrations of hydrogen [50,59,60]. Supporting evidence for the slip energy criterion has been shown on FAG-FE8 tests where WECs appeared firstly at areas of high frictional energy, this also being demonstrated in tests using angular contact ball bearings [29,58].…”
Section: Wec Initiation and Evolutionsupporting
confidence: 50%
“…Slip energy criteria have been linked to WSF, WSF occurring at areas of greatest PVmax. These areas have also been found to coincide with zones of highest concentrations of hydrogen [50,59,60]. Supporting evidence for the slip energy criterion has been shown on FAG-FE8 tests where WECs appeared firstly at areas of high frictional energy, this also being demonstrated in tests using angular contact ball bearings [29,58].…”
Section: Wec Initiation and Evolutionsupporting
confidence: 50%
“…hydrogen gas in fuel cells, water vapour in air) or from decomposition of lubricant (hydrocarbon-based oil and water molecules) on nascent metal surfaces generated by wear. In the high-stress, high-temperature conditions encountered in systems for supplying hydrogen such as compressors, both hydrogen gas and lubricant molecules (oil and solubilized water) can decompose on the fresh metal sites generated on the wear track and create atomic hydrogen 2,5,[10][11][12][13][14][15] . Severe lubrication conditions may produce more activated sites and increase hydrogen generation and diffusion in steel.…”
mentioning
confidence: 99%
“…Some of them suggest that hydrogen embrittlement is not due to brittle fracture 2,[6][7][8] , for example, Birnbaum and Sofronis 6) showed that hydrogen enhances localized plasticity and Nagumo et al 8) suggested that hydrogen increases atomic vacancies and causes unstable plasticity. In the case of rolling contact fatigue, there are some studies that have suggested that hydrogen generated by the decomposition of lubricant or water in the lubricant decreases the rolling contact fatigue life [9][10][11][12][13][14][15][16][17][18] . Some of them pointed that hydrogen causes microstructural change called white structure or white etching area (WEA) [15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%
“…In the case of rolling contact fatigue, there are some studies that have suggested that hydrogen generated by the decomposition of lubricant or water in the lubricant decreases the rolling contact fatigue life [9][10][11][12][13][14][15][16][17][18] . Some of them pointed that hydrogen causes microstructural change called white structure or white etching area (WEA) [15][16][17][18] . It suggested that types of lubricant, slip between rolling elements and rings, and static electricity affect hydrogen generation and diffusion into bearing steels.…”
Section: Introductionmentioning
confidence: 99%